Influence of P3HT preaggregation process on performance of the P3HT:C60-PCBM solar cells. (2nd November 2019) - Hibner-Kulicka, Paulina; Waliszewski, Witold; Borkowski, Michal; Luszczynska, Beata; Szymanski, Marek; Marszalek, Tomasz; Ulanski, Jacek
Abstract: The bulk heterojunction based created by poly(3-hexyltiophene-2, 5-diyl) (P3HT phenyl-C61-butyric acid methyl ester (C60-PCBM) it is well-known system used in organic solar cells. As the performance of such solar cells are very sensitive to the processing conditions of the active layers, we have focused attention to preaggregation process of P3HT in the aged solutions, which can be one of the reasons behind the different values of the reported efficiencies for this solar cell system. In this work, we present a systematic study of the influence of aging time of solutions mixture of P3HT:C60-PCBM in different solvents on the performance of the photovoltaic cells. The highest efficiency values were obtained from devices based on active layer dissolved in 1, 2-dichlorobenzene. These values were stable even after 120 h of aging solutions, which means that the solution ageing process does not affect the final device properties. While, in chloroform and toluene solvents, efficiency of solar cells decreases within aging process. Our processing approach allows to better understanding the relationship between morphology of P3HT:C60-PCBM layer and device performances.